Perkembangan Hukum Tata Negara Indonesia dan Implikasinya dalam Dimensi Negara Hukum (International Forum of Researchers and Lecturers, 2024)
The study is entitled The Development of The Indonesian State Law and Its Implications in The Dimension of The Rule of Law. This research begins with the formulation of Article 1 paragraph (3) of UUD 1945 which states that “The State of Indonesia is a state of law”. Described as a rule of law, Indonesia is responsible for always following the law as a means of achieving its goals. The law of the State that regulates the administration, government and institutions of the state is regarded as the foremost guard in achieving the ideals of a country. In its history, the Indonesian Civil Code has passed through many dynamics of all time and has arrived at the present time to dedicate its functions. However, the unavoidable development of the world makes the law including the Law of the State must always adapt to various developments. However, in its implementation the law of the state has always faced with various implications. For that, this study was written with the primary purpose of finding out how the Law of State Order has implicated its development in the modern era in the dimension of the rule of law. In completing his research, this paper uses the method of research of the juridic study with the data collection system of the study of the library.